1995
DOI: 10.1074/jbc.270.11.5823
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Chromosome Mapping of Human Galectin-7

Abstract: The galectins are a family of beta-galactoside-binding proteins implicated in modulating cell-cell and cell-matrix interactions. Here we report the cloning and expression of a novel member of this family (galectin-7) that correspond to IEF (isoelectric focusing) 17 (12,700 Da; pI, 7.6) in the human keratinocyte protein data base, and that is strikingly down-regulated in SV40 transformed keratinocytes (K14). The cDNA was cloned from a lambda gt11 cDNA expression library using degenerated oligodeoxyribonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 41 publications
1
122
1
2
Order By: Relevance
“…Xgalectin-Va and/or -Vb is the most abundant protein in skin (5% of the total protein) (26). In mammals, a proto-type galectin, galectin-7, is abundantly expressed in skin keratinocytes (12,37,38), but its amino acid sequence is dissimilar from that of either xgalectin-Va or -Vb. Thus, galectin(s) distributed in skin may have evolved independently in various animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Xgalectin-Va and/or -Vb is the most abundant protein in skin (5% of the total protein) (26). In mammals, a proto-type galectin, galectin-7, is abundantly expressed in skin keratinocytes (12,37,38), but its amino acid sequence is dissimilar from that of either xgalectin-Va or -Vb. Thus, galectin(s) distributed in skin may have evolved independently in various animal species.…”
Section: Discussionmentioning
confidence: 99%
“…22 Galectin-7 was originally identified in the human epidermis and later found to be expressed in all types of stratified epithelial cells in the skin, tongue, esophagus, and Hassal's corpuscles in the thymus. 20,21,25 In skin keratinocytes, its expression is rapidly induced following exposure to UV irradiation in association with p53 stabilization, and an increased level of the protein was mainly found in sunburned apoptotic keratinocytes. 24 Indeed, Kuwabara et al 46 have shown that stable transfectants of Hela cells expressing galectin-7 exhibit enhanced sensitivity to apoptosis.…”
Section: Figurementioning
confidence: 99%
“…Among those genes whose expression were significantly altered, we further investigated the unexpected and strongly upregulated galectin-7. This gene, originally identified as a keratinocyte marker, 20,21 has previously been associated with the development of chemically induced mammary carcinoma 22 and is one of the 14 genes previously shown to be under the control of p53. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Galectin-7 is expressed in stratified epithelial cells (8,9), but its expression is down-regulated in transformed keratinocytes and squamous cell carcinoma cells (8,10). Its gene was reported to be one of those highly induced by the tumor suppressor p53 in the human colon carcinoma cell line DLD-1, thus designated as p53-induced gene 1 (PIG1), and the protein has been suggested to play a role in the proapoptotic function of p53 (11).…”
Section: Introductionmentioning
confidence: 99%